Low intensity blood parasite infections do not reduce the aerobic performance of migratory birds - Hahn, Steffen; Bauer, Silke; Dimitrov, Dimitar; Emmenegger, Tamara; Ivanova, Karina; Zehtindjiev, Pavel; Buttemer, William A. (Proceedings of the Royal Society. B, Biological sciences, 2018)
Blood parasites (Haemosporidia) are thought to impair the flight performance of infected animals, and therefore, infected birds are expected to differ from their non-infected counterparts in migratory capacity. Since haemosporidians invade host erythrocytes, it is commonly assumed that infected individuals will have compromised aerobic capacity, but this has not been examined in free-living birds. We tested if haemosporidian infections affect aerobic performance by examining metabolic rates and exercise endurance in migratory great reed warblers (Acrocephalus arundinaceus) experimentally treated with Plasmodium relictum pGRW04 and in naturally infected wild birds over consecutive life-history stages. We found no effect of acute or chronic infections on resting metabolic rate, maximum metabolic rate or exercise endurance in either experimentally treated or free-living birds. Oxygen consumption rates during rest and while undergoing maximum exercise as well as exercise endurance increased from breeding to migration stages in both infected and non-infected birds. Importantly, phenotypic changes associated with preparation for migration were similarly unaffected by parasitaemia. Consequently, migratory birds experiencing parasitaemia levels typical of chronic infection do not differ in migratory capacity from their uninfected counterparts. Thus, if infected hosts differ from uninfected conspecifics in migration phenology, other mechanisms besides aerobic capacity should be considered.